Analysis of Student Errors in Solving Non Homogeneous Differential Equations Problems Based on Kastolan Stages - Aini, Septi Dariyatul; Irawati, Sri (JTAM (Jurnal Teori dan Aplikasi Matematika), 2022)
The purpose of this study is to identify and classify any errors made by students in solving problems of non-homogeneous order n differential equations and to find out what causes students to make errors in solving problems. This research is a qualitative descriptive research. The instruments used in this study were the Mathematical Ability Test, the Differential Equation Problem Solving Test and interview guidelines. The selection of subjects began by giving a math ability test to 35 students in the class. From the results of these tests, 3 students were then selected from a variety of errors to become research subjects. The criteria for selecting research subjects refer to: (a) the number of mistakes made by students in answering test questions; (b) variations in the types of errors made by students; (c) have the ability to communicate both orally and in writing; (d) willing to be interviewed. Based on the results of the study, information was obtained that the types of student errors in solving non-homogeneous order n differential equations based on the Kastolan stages were: (1) conceptual errors consisted of errors in the use of formulas in answering questions and using formulas that were not in accordance with the conditions or prerequisites for enactment formulas, (2) procedural errors consist of errors because they cannot solve the problem in the simplest form and errors because they cannot continue the completion step, (3) technical errors consist of errors in calculating the value of a arithmetic operation, errors in writing that there is constant or variable written wrong or forgot not to write or an error moving a constant or variable from one step to the next, and improperly substituting values into variables. While the factors that cause student errors in solving problems of non-homogeneous order n differential equations are students who do not understand the prerequisite materials needed to solve problems of non-homogeneous order n differential equations, do not understand the concept of determining the general form of a special solution with certain prerequisites, student skills in carrying out arithmetic operations they are still lacking, less thorough, in a hurry, and nervous so that there are several completion steps that are miscalculated, missed, not written down, and not converted to the simplest form.